Cognitive Profile Patterns Are Affected by Measurement Precision (Journal of Education and Development, 2021)
A necessary, albeit tacit assumption underlying pattern analysis of cognitive profiles is that an examinee’s profile pattern is not affected by the level of precision used in measuring the subtest, index or factor scores. We empirically test the truth of this assumption across various precision levels, such as IQ points (1/15SD), T-scores (0.1SD), scaled scores (1/3SD) and stanines (0.5SD). The results clearly refute the pattern stability assumption. They question the very uniqueness of profile patterns as a stable individual characteristic and challenge their use in both clinical practice and scientific research. Possible solutions are suggested and critically examined.